J. K. S. Makokha, Ogone John Obiero y Russell West-Pavlov (eds.), Style in African Literature: Essays on Literary Stylistics and Narrative Styles, Amsterdam, Rodopi, 2012, 441 pp. - Rosenberg, Aaron Louis (Estudios de Asia y África, 2015)
J. K. S. Makokha, Ogone John Obiero y Russell West-Pavlov (eds.), Style in African Literature: Essays on Literary Stylistics and Narrative Styles, Amsterdam, Rodopi, 2012, 441 pp.